Perancangan Sistem Gerak Semi Otomatis Pada Prototipe Mesin Frais Mini Berbasis Spindel Bor Tangan Dengan Arduino Dan Motor Stepper - Dicky Tria Prasetyo; Diah Wulandari (CV. SINAR HOWUHOWU, 2026)
The development of manufacturing technology and Industry 4.0 demands machine tools that are more efficient, precise, and affordable for educational purposes. However, conventional machines are still limited by high costs and dependence on operator skills, while laboratory-scale machines are not yet optimal in terms of accuracy and control systems. This study aims to design and build a semi-automatic mini milling machine prototype utilizing a hand drill as the spindle, stepper motors as axis actuators, and an Arduino as the main controller. The research method employed is a Research and Development (R&D) approach, which includes the stages of design, fabrication, and motion system testing. The design process began with the creation of a system block diagram and 2D/3D designs, followed by mechanical assembly and electrical system installation. Testing focused on motion accuracy and stability by comparing the theoretical values programmed in the Arduino IDE with the actual measurement results obtained from the test material. The research results indicate that the semi-automatic mini milling machine prototype is capable of operating effectively and achieving a high level of accuracy. In the testing of movement along the X and Y axes, the average accuracy levels obtained were 99.41% and 99.88%, respectively. Meanwhile, for the Z axis, the average accuracy levels were 97.91% for Z1 and 95.8% for Z2. These values indicate that the motion system is able to execute programmed commands with relatively small deviations and remains within acceptable tolerance limits for machining soft materials such as nylon or polyethylene.